IMPROVEMENT OF TECHNOLOGIES FOR THE DEVELOPMENT OF INNOVATIVE ACTIVITIES OF PEDAGOGUES BASED ON THE ACMEOLOGICAL APPROACH - Xamrayeva Diyora Burxon qizi (Journals Park Publishing, 2024)
In today's rapidly evolving educational landscape, the role of pedagogues in fostering innovation and creativity among students is paramount. This article explores the concept of acmeology and its application in enhancing the professional development of educators. Acmeology, a branch of psychology focused on the study of peak performance and excellence, offers valuable insights into the processes underlying effective teaching and learning. By integrating acmeological principles into pedagogical practice, educators can cultivate a culture of innovation, resilience, and continuous improvement in the classroom. This article discusses various technologies and strategies for implementing acmeological approaches in teacher training programs, curriculum design, and classroom instruction. Through a combination of theoretical insights and practical examples, it highlights the potential of acmeology to empower pedagogues to unlock their full potential and inspire excellence in their students.
Keywords: acmeology, pedagogy, innovation, professional development, teacher training, technology, creativity, peak performance, resilience, classroom instruction.